Enhancing Service Quality in Indonesian Food Cart Franchise: Assurance and Empathy For Franchisee Satisfaction - Wafa Syahidah; Zenal Asikin (School of Business, IPB University (SB-IPB), 2023)
The franchise business not only provides good products but also provides services that satisfy the franchisee. One of Indonesian company franchise, Arofah Kebab, is facing issues with franchises who inconsistenly purchase raw materials and inactive franchises. The problems may be caused by Arofah kebab’s inability to maintain the quality of services to its franchisees. Arofah Kebab has no information about the quality of its service. This study aims to analyze the level of importance and performance of Arofah Kebab services, and franchisee satisfaction. Respondents were 40 active franchisees (33% of total accessible population) using the convenience sampling method. Service attributes are determined by the servqual model and analyzed using descriptive analysis, customer satisfaction index (CSI), and importance-performance analysis (IPA). The results indicate that assurance and empathy dimensions are service quality dimensions that need to be futher emphasized by individual franchise businesses in providing services to frachisees. These dimensions encompass various service attributes that relate to assurance and the personal relationship between the franchise and franchisor. In the case of Arofah Kebab, four service attributes need to be improved including carrying out every obligation in the agreement, strengthening two-way communication, creating SOP for employees who deal directly with franchisees, and providing extensions for customer service hour and ensuring service operating hours run on time. Keywords: CSI, franchise, franchisee satisfaction, IPA, service quality